Serum NfL, but not GFAP, differentiates primary lateral sclerosis from adrenomyeloneuropathy and hereditary spastic paraplegia type 4 - Kessler, Christoph; Wilke, Carlo; Hengel, Holger; Rattay, Tim W.; Maleska Maceski, Aleksandra; Kuhle, Jens; Schöls, Ludger; Schüle-Freyer, Rebecca (Amyotrophic lateral sclerosis & frontotemporal degeneration, 2025)
Neurodegenerative upper motor neuron (UMN) syndromes ranging from primary lateral sclerosis (PLS) to pure and complicated types of hereditary spastic paraplegia (HSP) remain challenging to differentiate clinically, especially in the early stages of disease. As they share the hallmark of spastic paraparesis, easily accessible biomarkers are warranted to facilitate an early diagnosis. We examined serum neurofilament light chain (sNfL) and serum glial fibrillary acidic protein (sGFAP) as diagnostic biomarkers to differentiate PLS from HSP, represented by two paradigmatic subtypes: SPG4, the most common type of pure HSP, and adrenomyeloneuropathy (AMN), a common complicated form of HSP. In addition to sNfL and sGFAP raw levels, we used age-adjusted z-scores to account for age-related biomarker level increases. In our cohort of 18 PLS patients, 18 AMN patients, 25 SPG4 patients and 60 controls, sNfL z-scores were higher in PLS than in SPG4 (p < 0.001), AMN (p = 0.03), and controls (p < 0.001). Furthermore, sNfL z-scores allowed distinguishing PLS from SPG4 (AUC 0.82, 95% CI 0.67-0.98) and—slightly less accurate—from AMN (AUC 0.77, 95% CI 0.60-0.95). sGFAP z-scores did not differ significantly between groups. Our study suggests that serum NfL, but not GFAP, is a potential diagnostic biomarker in degenerative UMN diseases and may help to differentiate PLS from pure and complicated forms of HSP. Our results indicate that axonal degeneration—the source of NfL release—is predominant over astrocytic pathology—the source of GFAP release—in PLS, AMN, and SPG4.
Gesehen am 04.02.2026